2013
DOI: 10.1128/genomea.00576-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Variant of the Methicillin-Resistant Staphylococcus aureus ST239 Lineage, Strain BMB9393, Displaying Superior Ability To Accumulate ica -Independent Biofilm

Abstract: Biofilm is considered an important virulence factor in nosocomial infections. Herein, we report the complete genome sequence of a variant of methicillin-resistant Staphylococcus aureus, strain BMB9393, which is highly disseminated in Brazil. This strain belongs to the lineage ST239 and displays increased ability to accumulate ica-independent biofilm and to invade human epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Kuhn et al also found no difference with adhesion genes in epidemic and sporadic MRSA clones (Kuhn et al, 2006). Gene expression studies and whole genome sequencing may assist to elucidate the reason for these differences (Costa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Kuhn et al also found no difference with adhesion genes in epidemic and sporadic MRSA clones (Kuhn et al, 2006). Gene expression studies and whole genome sequencing may assist to elucidate the reason for these differences (Costa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that MRSA strains develop biofilm by a PIA-independent mechanism (McCarthy et al, 2015). In particular, the BRZ lineage displays increased ability to accumulate ica -independent biofilm (Costa et al, 2013). It is worth noting that increases in the PIA concentration due to the action of SAL on MRSA strains (both CBS and BRZ) resembled that of the MSSA (Newman) strains indicating that SAL induces PIA-mediated biofilms by S. aureus independently of the methicillin susceptibility status under the conditions studied.…”
Section: Discussionmentioning
confidence: 99%
“…), and its complete genome was sequenced by Costa et al . (). All strains were stored at −70°C in 10% glycerol.…”
Section: Methodsmentioning
confidence: 97%
“…Quinones are very important compounds, as they play a key role in living cells in the respiratory chain, blood coagulation and the carboxylation of glutamates (Thomson 1997). The relationship between quinones and the biochemical processes of infecting micro-organisms led to several studies searching for synthetic bioactive compounds with antiparasitic Jorqueira et al 2006;Silva-Jr et al 2008), molluscicidal (Gallagher 1996;Santos et al 2001;Barbosa et al 2005), leishmanicidal (Teixeira et al 2001), antifungal (Gafner et al 1996), trypanocidal (Pinto et al 2000;Pinto and de Castro 2009;Salas et al 2011), and antibacterial activities (Tandon et al 2005;Jordão et al 2013;Souza et al 2013).…”
Section: Introductionmentioning
confidence: 99%